Maskot Desa Wisata yang Menyatukan Warisan Budaya Bandung - Karya Inovatif KUKERTA UIN SMH Banten Kelompok 29 - Putri Melani; Lughoh Khofifah; Muthia Magrina; Hilda Khaerunnisa; Agus Sukirno (Lembaga Pengembangan Kinerja Dosen, 2024)
Bandung Village, which is rich in local traditions and culture, has launched the Dewi Sinyonya mascot as part of its tourism promotion strategy. This mascot, which is the work of KUKERTA UIN SMH Banten group 29 students, aims to connect the village's cultural heritage with the modern era. The name